2019
DOI: 10.1111/cod.13390
|View full text |Cite
|
Sign up to set email alerts
|

Positive change in hand care habits using therapeutic patient education in chronic hand eczema

Abstract: Background: Chronic hand eczema (CHE) is a major burden for patients. Maintenance treatment involves prevention measures limiting detrimental behaviour and aggravating factors.Objective: To evaluate the effect of a standardised care program including therapeutic patient education (TPE) on hand care behaviours, clinical severity, quality of life, and work productivity.Methods: A single-centre study was conducted prospectively. Together with the prescription of a topical steroid, patients participated in individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…108 In a French study that evaluated the benefit of therapeutic patient education in 72 adults with chronic hand eczema, 43.7% had a personal history of AD. 109 A retrospective review and clinical examination of 725 German adolescent and adults with AD found that two-thirds of patients whose dermatitis developed after infancy and then persisted into adulthood had hand dermatitis. 75 A systematic review and meta-analysis of 35 studies in 12 countries showed that patients with AD have a 3- to 4-fold increased incidence of hand dermatitis when compared with controls, 110 and that hand dermatitis in schoolchildren with AD frequently affects only the dorsa.…”
Section: Introductionmentioning
confidence: 99%
“…108 In a French study that evaluated the benefit of therapeutic patient education in 72 adults with chronic hand eczema, 43.7% had a personal history of AD. 109 A retrospective review and clinical examination of 725 German adolescent and adults with AD found that two-thirds of patients whose dermatitis developed after infancy and then persisted into adulthood had hand dermatitis. 75 A systematic review and meta-analysis of 35 studies in 12 countries showed that patients with AD have a 3- to 4-fold increased incidence of hand dermatitis when compared with controls, 110 and that hand dermatitis in schoolchildren with AD frequently affects only the dorsa.…”
Section: Introductionmentioning
confidence: 99%
“…Because women at this age have more access to water at workplace and housework, which may possibly damage the skin barrier. 30 The pathogenesis of AD is complex and multifactorial, with genetic predisposition, skin barrier dysfunction, altered immune responses, and environmental and lifestyle factors. 31 We further observed an upward trend in prevalence of AD among those aged 50þ.…”
Section: Discussionmentioning
confidence: 99%
“…Because women at this age have more access to water at workplace and housework, which may possibly damage the skin barrier. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic patient education is a non-pharmacological intervention that assists patients and their families in learning or maintaining relevant skills for managing life with a chronic disease [ 12 , 13 , 21 ], and has been well-studied in asthma, chronic hand eczema, and chronic heart failure [ 12 , 13 , 21 ]. Previous research supports the hypothesis that therapeutic patient education is essential to improving the knowledge of the asthma patient, self-management of the disease, and the prevention of attacks [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Asthma control is affected by multiple factors, which also require prevention measures to decrease negative behaviors and aggravating factors [ 8 , 9 ]. Previous studies provide evidence for the efficacy and efficiency of patient education and asthma self-management [ 10 , 11 ]; therapeutic patient education, which helps patients acquire or maintain the skills they need to self-manage a chronic disease [ 12 ], has been well-studied in asthma control in children [ 13 ]. However, whether therapeutic patient education is effective in improving asthma control in severe uncontrolled asthma cases is unknown.…”
Section: Introductionmentioning
confidence: 99%